2020
DOI: 10.1007/s00415-020-10189-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors, white matter lesions and cognitive impairment in Parkinson’s disease: the PACOS longitudinal study

Abstract: Background Vascular risk factors (VRFs) may be associated with cognitive decline in early Parkinson's disease (PD) but results are inconclusive. The identification of modifiable risk factors is relevant for prevention and treatment. Methods Parkinson's disease (PD) patients of the PACOS cohort who underwent a baseline and follow-up neuropsychological evaluation were enrolled in the study. PD with Mild Cognitive Impairment (MCI) and dementia (PDD) were diagnosed according to the MDS criteria. A Baseline 1.5 T b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…This finding needs further confirmation in larger prospective studies. Several following‐up studies 89,90 revealed that WMH on longitudinal changes may increase the risks for cognitive decline in PD. The greater baseline WMH burden showed, the more significantly cognitive decline in Parkinson's patients, suggesting baseline WMH burden could be the risk for future cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…This finding needs further confirmation in larger prospective studies. Several following‐up studies 89,90 revealed that WMH on longitudinal changes may increase the risks for cognitive decline in PD. The greater baseline WMH burden showed, the more significantly cognitive decline in Parkinson's patients, suggesting baseline WMH burden could be the risk for future cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease patients frequently suffer from mild cognitive impairment (MCI) (MoCA score more than 21 and less than 26) (Litvan et al, 2012), who are at higher risk of developing dementia compared to PD patients with normal cognition (PD-NC) (Kehagia et al, 2010). Several lines of evidence suggested the inflammatory risk factors (Trefoil Factor 3,neutrophils,lymphocytes,et al) in PD may modulate underlying neurodegeneration particularly in relation to dementia (Stojkovic et al, 2018;Zou et al, 2018;Nicoletti et al, 2020;Wang et al, 2020). It is promising to detect MRI-visible EPVS burden as a marker of cognitive decline in PD.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that polymorphisms in RAS genes may exert an indirect influence on cognitive decline in PD. Some studies revealed a correlation between white matter hyperintensities (WMH) seen in magnetic resonance imaging with dementia in PD [31][32][33]. Taylor et al [34] analysed polymorphisms in both angiotensin II receptors genes: A1166C (rs5186) in AGTR1 and C3123A (rs2148582) in AGTR2.…”
Section: Discussionmentioning
confidence: 99%